2014
DOI: 10.1021/jo5018074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Properties of Supramolecular Photoswitches Based on Ammonioalkyl Derivatives of Crown Ether Styryl Dyes

Abstract: The synthesis of new styryl dyes derived from 4-pyridine and 4-quinoline and having an ammonioalkyl N-substituent and benzocrown ether moieties of different sizes and with different sets of heteroatoms was developed. Spontaneous "head-to-tail" dimerization of these dyes via the formation of numerous hydrogen bonds between the terminal NH3(+) groups and crown ether moieties was detected in MeCN solutions. The stability constants of the dimeric complexes having pseudocyclic structure were studied by (1)H NMR tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 44 publications
3
37
0
Order By: Relevance
“…1 H NMR titration is a useful method to identify interaction between different molecules by determining chemical shift of hydrogen atoms (Gromov et al, 2014;Liu et al, 2015). The interactions between compounds 1a-3a and tyrosinase were further observed from 1 H NMR titrations in DMSO-d 6 .…”
Section: H Nmr Titration Studiesmentioning
confidence: 99%
“…1 H NMR titration is a useful method to identify interaction between different molecules by determining chemical shift of hydrogen atoms (Gromov et al, 2014;Liu et al, 2015). The interactions between compounds 1a-3a and tyrosinase were further observed from 1 H NMR titrations in DMSO-d 6 .…”
Section: H Nmr Titration Studiesmentioning
confidence: 99%
“…Our previous investigations [3][4][5][6][7]17,18,28,45,46 have shown that brightly colored protonated styrylheterocycles and quaternary salts of styrylheterocycles (styryl dyes) Het + -CHCH-Ar X − (X − = I − , ClO 4 − , BF 4 − , TsO − ) are very suitable species for studying PCA reaction in the solid state, including the "single crystal-to-single crystal" (SCSC) processes (i.e., the processes that proceed without single crystal destruction). First their advantage is the potential to create the stacking packing motifs 1 or 2, and the rarely parallel-dimeric motifs 3 or 4.…”
Section: Introductionmentioning
confidence: 97%
“…The PCA reaction is also challenging for creation of information optical recording systems. [3][4][5][6][7]9,[17][18][19][20]22,28,29,38,43,45,46 In studies of PCA reactions it is important to a priori achieve the formation of a "pre-organized" dimeric pair which shows the stacking interaction of the two molecules. 49 However, these reactions are thermal and they proceed in solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9] The most peculiar photochemical processes taking place in these supramolecular systems with significant changes in the properties are trans-cis-photoisomerization and [2+2]-photocycloaddition (PCA) reactions. [10][11] Consequently, it is possible to control the receptor properties of bis-crown ethers through photochemical modification of the labile central moiety.…”
Section: Introduction Formulation Of the Problem Scope Of Objectivesmentioning
confidence: 99%